Застосування методів ситуаційного управління в складних системах для прийняття рішень в умовах позаштатних ситуацій - Швед, Альона Володимирівна; Давиденко, Євген Олександрович; Shved, Alyona; Davydenko, Yevhen (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Метою роботи є дослідження нових підходів спрямованих на вирішення задачі синтезу та прийняття ефективних рішень в складних системах. Розглянуто питання застосування методів ситуаційного моделювання для забезпечення підтримки процесів прийняття рішень в умовах позаштатних ситуацій. Дістав подальшого розвитку CBR-підхід на основі математичного апарату теорії грубих множин. Запропонований підхід дозволяє розбивати базу прецедентів на класи за ступенем приналежності прецеденту до сформованої цільової множини, що в свою чергу забезпечує можливість звуження множини пошуку прототипів рішень, які відповідають параметрам поточної проблемної ситуації. Запропонований підхід становить теоретичну основу для побудови інтелектуальних систем підтримки прийняття рішень у складних системах управління. /// EN: The process of synthesis and decision-making in complex social, economic, technical, organizational, and other systems typically occurs under a high level of uncertainty, a dynamic external and internal environment, limited time and resources, and a significant number of contradictory factors that describe the complex processes occurring in such systems. The situation becomes more complicated when addressing strategic, long-term, complex problems, which are often poorly structured, difficult to formalize and solve rigorously theoretically. The paper considers the application of situational modeling methods to support decision-making processes in complex systems for extraordinary situations solving. Situational modeling methods allow overcoming the mentioned difficulties and problems in solving weakly structured or partially formalized tasks that arise in complex systems, leveraging the accumulated professional experience of specialists in a given subject area. The paper considers the possibility of using of the case based reasoning method to provide support for decision-making processes in extraordinary situations. A modification of the CBR approach has been proposed based on the mathematical apparatus of rough set theory. The proposed approach involves defining approximations of the target set of precedents for the purpose of classifying precedents and subsequently searching for them in the database of precedents. Which in turn allows narrowing the search set of solution prototypes that match the parameters of the current problem situation, which in turn helps reduce the time required to solve the classification and search problems. The use of rough set theory methods allows for acquisition and processing of knowledge about precedents generated under uncertainty and the presence of imprecise, raw, contradictory source data. The proposed approach provides a theoretical basis for building intelligent decision support systems in complex management systems.
Situational management in complex systems for emergency decision-making: application and approaches
Keywords: ситуаційне моделювання; проблемна ситуація; метод міркувань за прецедентами; теорія грубих множин; апроксимація цільової множини; situational modeling; abnormal situation; case-based reasoning; rough set theory; approximation of the target set